2022
DOI: 10.3389/fimmu.2021.760021
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Semantic Variant of Primary Progressive Aphasia Associated With Anti-Glial Fibrillary Acid Protein Autoantibodies

Abstract: BackgroundFrontotemporal lobar degeneration is a heterogeneous disorder entailing a semantic variant of primary progressive aphasia (svPPA). A subtype of frontotemporal dementia associated with glutamate receptor subunit 3 (GluA3) antibody of the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) was recently identified. Here, we describe the novelty of a svPPA associated with anti-glial fibrillary acid protein (GFAP) antibodies.MethodsTo diagnose this 68-year-old woman we conducted a clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
(43 reference statements)
1
0
1
Order By: Relevance
“…As a subtype of frontotemporal dementia (FTD), svPPA is characterized by semantic language impairment and by predominant left anterior temporal atrophy on brain MRI . It has been previously reported that glial fibrillary acid protein autoantibodies were detected in a patient with svPPA . The verbal and cognitive functions of the patient in the present study improved after immunotherapy, whereas the previous patient did not respond.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…As a subtype of frontotemporal dementia (FTD), svPPA is characterized by semantic language impairment and by predominant left anterior temporal atrophy on brain MRI . It has been previously reported that glial fibrillary acid protein autoantibodies were detected in a patient with svPPA . The verbal and cognitive functions of the patient in the present study improved after immunotherapy, whereas the previous patient did not respond.…”
supporting
confidence: 91%
“…1 It has been previously reported that glial fibrillary acid protein autoantibodies were detected in a patient with svPPA. 2 The verbal and cognitive functions of the patient in the present study improved after immunotherapy, whereas the previous patient did not respond. SQSTM1 variants were identified in patients with FTD.…”
contrasting
confidence: 46%